1991
DOI: 10.1152/ajpheart.1991.260.6.h1935
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen metabolites inhibit spontaneous lymphatic contractions

Abstract: The effects of oxygen-derived free radicals on the contractile activity of the mesenteric collecting lymphatics were evaluated in the anesthetized rat. Lymphatic contractions were monitored before, during and after the application of oxyradicals. Contraction frequency (F), stroke volume (SV), ejection fraction (EF), contraction propagation (PC), and lymph pump flow (LPF) were determined from the lymphatic diameter tracings. Oxyradicals were generated using hypoxanthine and xanthine oxidase. Exposure to oxyradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 18 publications
4
65
0
Order By: Relevance
“…This result may be a contributing factor to the elevated ROS in aged vessels and/or may augment the oxidative stress on the vessels during aging, leading to elevated levels of oxidative damage. In parallel with data obtained by Zawieja et al, 65 we propose that diminished SOD enzyme activity may play an important role in development of the aging-associated impairment of the mesenteric lymph transport function reported by us earlier. 24,30 However, further functional investigations are necessary to confirm the role of SOD protein dysfunction during aging in mesenteric lymphatic vessels.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This result may be a contributing factor to the elevated ROS in aged vessels and/or may augment the oxidative stress on the vessels during aging, leading to elevated levels of oxidative damage. In parallel with data obtained by Zawieja et al, 65 we propose that diminished SOD enzyme activity may play an important role in development of the aging-associated impairment of the mesenteric lymph transport function reported by us earlier. 24,30 However, further functional investigations are necessary to confirm the role of SOD protein dysfunction during aging in mesenteric lymphatic vessels.…”
supporting
confidence: 91%
“…[62][63][64] The balance between the levels of free radical production and cellular antioxidant activity determine the oxidative stress on the tissue and subsequent degree of oxidative damage. Importantly, Zawieja et al reported 65 that oxygen radicals significantly inhibited contractile activity of rat mesenteric lymphatic vessels; thus we propose that agingassociated increases in oxidative stress could contribute to the decline in contractile activity seen in aged lymphatic vessels. Currently, there are no investigations of aging-associated oxidative stress or oxidative damage in lymphatic vessels.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The data were collected in 3-5 min intervals at each set of inflow-outflow pressures. From the lymphatic diameter tracing we used cardiac pump analogies to define systolic and diastolic lymphatic diameters in reference to the lymphatic contractile cycle (Benoit et al 1989;Zawieja et al 1991). At the end of each experiment, the passive (relaxed) diameters were measured at each pressure after the vessels were exposed to a nominally calcium-free (EDTA, 3.0 mM) APSS for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although a few studies have measured maximal active stress in bovine and porcine lymphatics (2,15,16,32), the maximal contractility of mesenteric lymphatics has not been determined for the rat, which is the model used for many in vivo lymphatic and microcirculation studies (3,5,(51)(52)(53). Furthermore, comparisons between arterial, venous, and lymphatic vessels in the same vasculature do not exist.…”
mentioning
confidence: 99%